Analisis Faktor yang Mempengaruhi Minat Berkunjung Ulang Wisatawan ke Objek Wisata Istano Basa Pagaruyung - Putri Yani, Wewel; Febria Rahim; Novia Nengsih; Harry Yulianda; Vinny Helvira (UIN Mahmud Yunus Batusangkar, 2025)
The main issue in this study is based on visitation data showing a decline in the number of tourists to the Istano Basa Pagaruyung tourist attraction in 2023–2024. In addition, aspects of tourist attraction, facilities, and accessibility are not yet optimal, which has the potential to reduce tourists' interest in revisiting. This study aims to determine and analyze the effect of tourist attraction (X1), facilities (X2), and accessibility (X3) on the interest in revisiting (Y) the Istano Basa Pagaruyung tourist attraction. The method used in this study is quantitative. The sampling technique used purposive sampling with a sample size of 97 people. The data collection technique in this study was conducted by filling out a questionnaire that had been tested for validity and reliability. The data analysis technique used was multiple linear regression analysis. The results of hypothesis testing show that, partially, tourist attraction has a significant positive effect on repeat visit interest with a t-value of 8.847 > t-table of 1.661 with a significance value of 0.000 < 0.05, so that hypothesis H1 can be accepted. Facilities do not affect repeat visit interest, with a t-value of 1.925 > t-table of 1.661 and a significance value of 0.057 > 0.05, so hypothesis H2 is rejected. Accessibility has a significant positive effect on repeat visit interest with a t-value of 3.485 > t-table of 1.661 with a significance value of 0.001 < 0.05, so hypothesis H3 can be accepted. The variables of tourist attraction, facilities, and accessibility simultaneously have a positive effect on repeat visit interest with a calculated F value of 130.080 > F table 2.70 and a significance of 0.000 < 0.05, so hypothesis H4 can be accepted.